Crosslinking of binary blends of ethylene/vinyl acetate copolymer and low density polyethylene or metallocene polyolefin elastomer as heat-shrinkable materials - Kudła, S. (Polimery, 2009)
The results of investigation of selected properties of peroxide crosslinked binary blends of ethylene/vinyl acetate copolymer and low density polyethylene or metallocene polyolefin elastomer as candidates for production of heat-shrinkable materials were presented. Analytical methods used - i.e. gel content, hot set test and rheometric investigations - as the measures of crosslinking degree, oxidation induction time and tensile properties measurements, before and after accelerated degradation, proved that the tested recipes were good starting points for further technological work. Some aspects of analytical determination of crosslinking degree are discussed.